The Development of the “BEYB” Defensive Tactics Model in Futsal Games - Benny Badaru; Nur indah atifah anwar; Ilham Azis; Hasby Asyhari (STAI Hubbulwathan Duri, 2022)
Futsal is a game that requires rapid transitions between offensive and defensive methods. The objective of this research is to build a futsal defensive strategy. This study employs a method of development using a model of development created by Brog and Goll. The development phase begins with problem analysis, followed by product design, validation of the designed model, product revision and testing, revision of product test findings, and the obtained model. The expected development is a model for developing futsal defensive strategies known as